Perceived social support mediates the association between attachment and cardiovascular reactivity in young adults. (25th October 2019) - McMahon, Grace; Creaven, Ann‐Marie; Gallagher, Stephen
Abstract: To understand the influence of social relationships on cardiovascular responses to stress, the present study investigated perceived affectionate support as a mediating variable explaining the association between specific attachment bonds (i.e., mother, father, partner, best friend) and cardiovascular reactivity (CVR). Utilizing a standardized stress testing protocol, 138 young adults completed measures of attachment and social support, with continuous cardiovascular measurements obtained using the Finometer Pro hemodynamic monitor. Results showed that the association between anxious and avoidant attachment and reactivity were mediated by perceived affectionate support; insecure attachment was linked to lower levels of perceived social support, which in turn was associated with lower CVR. For anxious attachment, this was noted only for mothers (SBP: B = −0.94, 95% CI [−1.94, −0.20]; DBP: B = −0.57, [−1.27, −0.10]), fathers (SBP: B = −0.72, [−1.42, −0.17]; DBP: B = −0.48, [−1.01, −0.13]), and best friends (SBP: B = −0.64, [−1.23, −0.18]; DBP: B = −0.40, [−0.81, −0.12]). For avoidant attachment, it was evident only for fathers (SBP: B = −0.70, [−1.33, −0.17]; DBP: B = −0.48, [−0.92, −0.15]) and partners (SBP: B = −0.78, [−1.64, −0.09]; DBP: B = −0.53, [−1.10, −0.11]). These findings suggest that insecure attachment is associated with lower levels of reactivity, which have been linked to negative health outcomes such as poor self‐reported health, depression, and obesity. Overall, this research expands on the support and relationship science literature by incorporating under‐researched aspects of social relationships (i.e., specific attachment styles) and focusing on the mechanisms by which they are associated with physiological stress responses. Abstract : This research extends the social support‐reactivity literature by focusing on the role of specific relationship figures (mother, father, partner, best friend) attachment in understanding the health benefits of social relationships—an area often overlooked within the health psychology literature. Importantly, this may provide insights into the mixed findings within the social support research. Moreover, given the methodological limitations of global measures of attachment, this study considers variations across different key relationship figures on a continuous measure.